2014
DOI: 10.1016/j.jep.2014.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Are plants used for skin care in South Africa fully explored?

Abstract: Graphical AbstractScientific validation of South African medicinal plants used traditionally for skin care and their pharmacological properties associated with treating skin conditions. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 148 publications
0
95
0
Order By: Relevance
“…Skin is the main structure that protects human body from the environmental factors and has, in addition, a relevant relationship to person aspect and beauty (Lall and Kishore, 2014). This is why applications for the skin are amongst the most important objectives of pharmaceutical industries, both with regard to dermatological pathologies as well as to cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…Skin is the main structure that protects human body from the environmental factors and has, in addition, a relevant relationship to person aspect and beauty (Lall and Kishore, 2014). This is why applications for the skin are amongst the most important objectives of pharmaceutical industries, both with regard to dermatological pathologies as well as to cosmetics.…”
Section: Introductionmentioning
confidence: 99%
“…39 In Ayurveda medicine, A. vera is known as the treatment for skin diseases. 40 For instance, A. vera leaves are usefull for skin burns. 41,42 However, some studies reported the weak allergenic potential of A. vera.…”
Section: Correlation Between Climatic Characteristics Of the Study Armentioning
confidence: 99%
“…41,42 However, some studies reported the weak allergenic potential of A. vera. 43,44 An additional, A. vera has been exhibited excellent pharmacological and cosmetic relevance and has been explored for skin hyperpigmentation problems. 45 For instance, actually A. vera was formulated in an aqueous based gel system for topical therapy of wild acne vulagris.…”
Section: Correlation Between Climatic Characteristics Of the Study Armentioning
confidence: 99%
“…These kinds of tyrosinase inhibitors are widespread in nature and botanical extracts are good source of naturally occurring tyrosinase inhibitors which are commonly used as traditional remedies for pigmentation disorders [67][68].…”
Section: Inhibition Of Tyrosinase Activitymentioning
confidence: 99%